Pengetahuan, Sikap, Kesadaran dan Harapan Pegawai Terhadap Eksistensi Komite Etik dan Hukum di RSUD Dr.Zainoel Abidin Banda Aceh - Suryadi, Taufik; Nurul A’la; Kulsum (LITBANG RSUDZA, 2021)
The main purpose of hospital services is to provide quality, professional and acceptable services to the community. One of the efforts to achieve quality and professional health services in hospitals is to comply with the rules listed in the Hospital Code of Ethics. Hospital Ethics and Legal Committee (HELC) can be an effective means of seeking mutual understanding between the various parties involved such as doctors, nurses, other health workers, patients, patients' families and the community regarding various ethical, legal, and medical issues in hospitals. The success of the health care system depends on health workers who are equipped with good knowledge, positive attitudes, and full awareness of the existence of HELC. So that research is needed that can be input for improving the performance of HELC in the future. The priority problem that will be resolved is the improvement of the HELC service system by gathering information from selected employees who are willing to become respondents. The type of this research is observational analytic with cross sectional approach. This study aims to obtain information about the level of knowledge, attitudes, awareness and expectations of the employees of Zainoel Abidin Hospital (ZAH) Banda Aceh on the existence of the HELC. This research was conducted for 4 months, starting from May to October 2021 at ZAH starting from the preparation of proposals to seminars on research results. This study involved all employees of ZAH who were selected proportionally for each profession and type of work with 280 participants. A total of 273 people (97.5%) have very good/good knowledge related to HELC. A very positive attitude towards HELC performance was shown by 245 respondents (87.5%). A total of 118 respondents have a high awareness of the existence of HELC (42.1%), while respondents' opinions about the importance of the existence of HELC obtained 263 respondents stated that it is very important/important (93.9%). From the results of the Chi square statistical test, it was found that there was a significant relationship between knowledge and the existence of HELC with p value = 0.000, attitude and existence of HELC with p value = 0.000, but there was no relationship between awareness and existence of HELC with p value = 0.352. The conclusion in this study was that the employees of ZAH had very good knowledge, a very positive attitude, but were not aware of the existence of the HELC of ZAH. The expectations expressed by the respondents concentrated to the socialization of HELC activities, improving performance, increasing active roles in hospital services and being able to work in accordance with standard operating procedures.